Software defined wireless sensor networks and efficient congestion control. Issue 6 (1st November 2018) - Letswamotse, Babedi Betty; Malekian, Reza; Chen, Chi‐Yuan; Modieginyane, Kgotlaetsile Mathews
Abstract : To achieve greater performance in computing networks, a setup of critical computing aspects that ensures efficient network operation needs to be implemented. One of these computing aspects is quality of service (QoS). QoS capable of networking allows efficient control of traffic, especially for network critical data. However, to achieve this in wireless sensor networks (WSNs) is a serious challenge, since these technologies have computing limitations. It is even difficult to manage networking resources with ease in these types of technologies, due to their communication, processing and memory limitations. Even though this is the case with WSNs, they have been largely used in monitoring/detection systems, and by this proving their application importance. In this study, a resource‐aware OpenFlow‐based active network management QoS scheme that uses software defined networking (SDN) strategies is proposed and implemented to apply QoS requirements for managing traffic congestion in WSNs. This scheme uses SDN programmability strategies to apply network QoS requirements and perform traffic load balancing to ensure congestion control in software defined WSNs. The experimental results show that the developed scheme is able to provide congestion avoidance within the network. It also allows opportunities to implement flexible QoS requirements based on the system's traffic state.